Educational Strategies in Zakat Fundraising at BAZNAS North Lombok Regency - Arifin, Ernaldo Fikrul; Shabran, M. Zainuddin (Business Management, 2026)
This study aims to describe the educational strategies used by the National Zakat Agency (BAZNAS) of North Lombok Regency to increase zakat socialization funding through educational and awareness approaches. This study found that BAZNAS' educational strategies include direct outreach in mosques and religious study groups, the use of social media and digital channels, and seasonal campaigns based on religious momentum. This approach has proven effective in increasing the understanding and participation of the Muslim community in paying zakat formally through official institutions. This study used a qualitative descriptive method with interview, observation, and documentation techniques. The results show that educational strategies play a significant role in building collective awareness, increasing public trust, and strengthening BAZNAS' legitimacy as a professional and trustworthy zakat management institution.